2020
DOI: 10.22616/erdev.2020.19.tf211
|View full text |Cite
|
Sign up to set email alerts
|

Evaporative cooling technology efficiency compared to traditional cooling system – case study

Abstract: The aim of the paper is to analyse evaporative cooling technologies used in the cooling system and to compare their energy efficiency with traditional cooling systems. Heating and cooling is the most significant energy end-use sector, accounting for about 40 % of total energy demand in the EU. The Member States must achieve cumulative end-use energy savings equivalent to new savings of 0.8 % from final energy consumption in the period and beyond. Therefore, the EU forces buildings and industries to shift to ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Studies have shown that if the cylinder of the compressor connected to the expander through the regenerator and cold head without intermediate valves (Fig. 1) provide cooling fins for heat exchange with the environment, and introduce the piston expander into direct heat exchange with the cooled body (load), and at the same time the system will be in thermal insulation, then a functional cascade of devices of this type allows you to achieve even lower temperatures with high efficiency [9,11,13,18,19].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that if the cylinder of the compressor connected to the expander through the regenerator and cold head without intermediate valves (Fig. 1) provide cooling fins for heat exchange with the environment, and introduce the piston expander into direct heat exchange with the cooled body (load), and at the same time the system will be in thermal insulation, then a functional cascade of devices of this type allows you to achieve even lower temperatures with high efficiency [9,11,13,18,19].…”
Section: Methodsmentioning
confidence: 99%
“…However indoor air quality and thermal comfort has a direct impact on personal productivity and ability to concentrate on duties and affect the decision making in stress conditions. European legislation is forcing buildings and industry to switch energy systems to efficient, decarbonize and renewable based [1]. In order to maintain a healthy and comfortable environment for the occupants of the building, it is important to maintain a good indoor environment with highly efficient building envelopes and energy systems [2].…”
Section: Introductionmentioning
confidence: 99%